2003
DOI: 10.1177/1073191103258591
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Forensic Mental Health Assessment

Abstract: Forensic mental health assessment (FMHA) is a form of evaluation performed by a mental health professional to provide relevant clinical and scientific data to a legal decision maker or the litigants involved in civil or criminal proceedings. Such FMHA evaluations can be further specialized when the clinical and scientific data are primarily neuropsychological. This paper provides an adaptation of 29 recently derived principles of FMHA (Heilbrun, 2001) that have been described in two forms: general guidelines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 15 publications
0
122
0
1
Order By: Relevance
“…Forensic reports provide a record that may be needed in the future as legal evidence if the case is reviewed. At minimum, there are four essential types of information that a forensic report must have to fulfill this obligation (for support for the following, see generally Grisso, 2004;Heilbrun et al, 2002;Melton, Petrila, Poythress & Slobogin, 2007).…”
Section: Producing a Legal Documentmentioning
confidence: 99%
“…Forensic reports provide a record that may be needed in the future as legal evidence if the case is reviewed. At minimum, there are four essential types of information that a forensic report must have to fulfill this obligation (for support for the following, see generally Grisso, 2004;Heilbrun et al, 2002;Melton, Petrila, Poythress & Slobogin, 2007).…”
Section: Producing a Legal Documentmentioning
confidence: 99%
“…The use of a model can have a direct impact on several areas of forensic mental health assessment ("FMHA"), and is important in gathering and interpreting data, reasoning about the results and conclusions, and communicating the results of such an assessment (Heilbrun, 2001;Heilbrun, Marczyk, & DeMatteo, 2002). Although the nature of the applicable model varies with the legal issue and psychological constructs being addressed, a model is most effective when it identifies the nature of the relevant data and reasoning needed in FMHA.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…relationship-or nexus-between clinical symptoms and functional legal deficits and competencies (Heilbrun, Marczyk, & DeMatteo, 2002). For example, the forensic clinician should begin by gathering data about relevant mental health and cognitive deficits or impairments as they relate to the legal issue under consideration.…”
Section: Journal Of Forensic Psychology Practicementioning
confidence: 99%
“…The psychologist should advocate for his or her data and conclusions, not for any litigant. Among the means of maintaining impartiality for the evaluator are (1) set and maintain professional boundaries regarding the retaining attorney; (2) avoid becoming invested in a particular outcome of a case; (3) communicate the results of the evaluation clearly and in simple language, avoiding superlatives (e.g., "absolutely" or "completely"), in both the report and testimony (Finch et al 2008;Greenberg 2003;Heilbrun et al 2002;Kane 2007b;Macartney-Filgate and Snow 2004;Melton et al 2007; see also the Specialty Guidelines for Forensic Psychologists, Guidelines VII.B, C, and D). According to Murphy (2000, p. 6), the American Bar Association has indicated that expert witnesses must be independent, rather than loyal to or an advocate for his or her client, the attorney.…”
Section: Conflicting Roles Of Therapist and Forensic Evaluatormentioning
confidence: 99%